2003
DOI: 10.1093/ndt/gfg146
|View full text |Cite
|
Sign up to set email alerts
|

Personal dialysis capacity (PDCTM) test: a multicentre clinical study

Abstract: In summary, the present study shows that the PDC(TM) program is a robust, accurate method to describe the peritoneal membrane transport characteristics. Analysis of PDC(TM) data of large groups of patients, especially if followed up over time, can give interesting information on the physiology of the peritoneal membrane and the impact of different parameters on it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…In all patients, a standard PDC test was performed during the first 3 mo of their PD treatment. The PDC test was performed as described earlier (15). In brief, patients were visited at home and given the instructions for the PDC regimen (five exchanges) and the collection of the dialysate samples and 24-h urine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all patients, a standard PDC test was performed during the first 3 mo of their PD treatment. The PDC test was performed as described earlier (15). In brief, patients were visited at home and given the instructions for the PDC regimen (five exchanges) and the collection of the dialysate samples and 24-h urine.…”
Section: Methodsmentioning
confidence: 99%
“…The PDC test-derived A0/dX is superior to the PET-derived dialysate over plasma concentration (D/Pcrea) to describe the transport of small solutes through the peritoneal membrane (14). The PDC test has been validated to describe membrane characteristics in large patient groups, both in adults and in children (15,16). The PDC test has also been advocated to describe the evolution of the functional capacity of the peritoneal membrane over time (17,18).…”
mentioning
confidence: 99%
“…Van Biesen et al (23) found this difference and asserted that the final part of the curve of the PDC peritoneal volume depended strongly on the volume drained after the long overnight dwell. If that drain is incomplete, the PDC reabsorption will be overestimated.…”
Section: Discussionmentioning
confidence: 97%
“…The pore model derived the description and relationships between the transport parameters from the solute size and the structure of the transport barrier (size of pores, number of pores etc.). The mentioned models of peritoneal transport were included into practical methods and computer programs for the evaluation of the efficacy and adequacy of peritoneal dialysis (Haraldsson, 2001;Van Biesen et al, 2003;Van Biesen et al, 2006;Vonesh et al, 1991;Vonesh &Keshaviah, 1997;Vonesh et al, 1999). In this chapter these two most popular models describing peritoneal transport of fluid and solutes were presented and compared as regards their basic ideas and aims as well as their applicability.…”
Section: Discussionmentioning
confidence: 99%